ANALISIS PERIODE GETAR ALAMI BANGUNAN MENGGUNAKAN MIKROTREMOR - Rezqya Mustika; Rusnardi Rahmat Putra; Ressy Fitria (Universitas Kristen Maranatha, 2022)
The natural vibrating period (T) of the structure, which is the time for the building structure to travel a complete turn of a vibration that undergoes a static equilibrium position shift and returns to its initial position, is an important component in the planning of earthquake-resistant buildings. Based on research conducted on several buildings in California (USA) to estimate the value of T, the equation of T was produced T=ζ.N, where N is the number of building floors and the constant ζ is 0.1 (SNI-1726 2019). However, this equation has been used for quite a long time and needs to be updated. Thus, the objective of this study is to update the equation using the result of microtremor measurements on buildings in Padang City, Indonesia. The microtremor measurements generated an accurate T, which resulted from the experimentally obtained period (T). The produced T values are arranged based on the building floor, i.e. 0.298, 0.298, and 0.306 for T value of the 2nd floor to 4th floor, respectively. From those T values, an updated equation was obtained, namely T = 0.0039N + 0.2933, where T is the natural period and N is the number of building floors.